Metaphors for Scripture: taking up Dale Martin’s challenge - Thompson, Geoff (Theology, 2020)
New Testament scholar Dale Martin has called for doing away with speaking of the ‘authority of Scripture’. Constructively, he proposes a number of metaphors for Scripture, which, nevertheless, point very strongly to the Church’s dependence on it. This article brings Martin’s programmatic suggestions into conversation with some recent doctrinal writing on Scripture that has given attention to the ‘what’ and ‘why’ of Scripture. The doctrinal reflections pose the question of what it is about Scripture that makes the Church dependent on it and to what end. The article suggests two metaphors that help illuminate the ‘what’ and ‘why’ of Scripture.